2009
DOI: 10.1007/s10560-009-0179-8
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of the Effectiveness of Attachment Therapy for Adopted Children with Reactive Attachment Disorder

Abstract: The purpose of this preliminary investigation was to examine the effectiveness of attachment therapy for adopted children diagnosed with Reactive Attachment Disorder (RAD). Although attachment therapy is widely utilized in the practice community, outcomes of such therapy have not been well documented. In this study a pretest-posttest one-group design was used with a sample of 24 adopted children who received attachment therapy from trained, licensed therapists. Therapy was funded by the Georgia Office of Adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…The grant-funded therapy program served as a resource for adoptive parents of children with severe emotional disturbance and was designed to promote attachment between the parents and their children. Although a mixed-methods program evaluation (Wimmer et al 2003) at the end of the program revealed improved child behavior scores (Wimmer et al 2009), funding for continued treatment was terminated, leaving the parents with deep feelings of frustration. This study sought to explore the mothers' perceptions of therapy and its impact on the family unit 3 years after therapy was terminated.…”
Section: Introductionmentioning
confidence: 99%
“…The grant-funded therapy program served as a resource for adoptive parents of children with severe emotional disturbance and was designed to promote attachment between the parents and their children. Although a mixed-methods program evaluation (Wimmer et al 2003) at the end of the program revealed improved child behavior scores (Wimmer et al 2009), funding for continued treatment was terminated, leaving the parents with deep feelings of frustration. This study sought to explore the mothers' perceptions of therapy and its impact on the family unit 3 years after therapy was terminated.…”
Section: Introductionmentioning
confidence: 99%
“…That is, an insecure child-parent attachment relationship has been shown to be associated with both internalizing (Brumariu and Kerns 2010 ; Colonnesi et al 2011 ; Goos et al 2013 ; Groh et al 2012 ; Madigan et al 2012 ) and externalizing problem behavior (Fearon et al 2010 ; Hoeve et al 2012 ). Fortunately, there is also a vast body of empirical evidence showing that attachment insecurity can be treated effectively (Bakermans-Kranenburg et al 2003 , 2005 ; Cornell and Hamrin 2008 ; Wimmer et al 2009 ; Zeanah et al 2005 ).…”
mentioning
confidence: 99%
“…Academic and professional publications attest to the practice among some clinicians of linking conduct problems in the context of maltreatment to attachment disorders (e.g., Becker‐Weidman, ; Hall & Geher, ; Hughes, ; Randolph, ; Thomas, ; Vasquez & Miller, ; Wimmer et al., ), a link that does not reflect the clinical consensus as codified in DSM‐5 and ICD‐10 or ICD‐11. The current study did not have access to the clinical reasoning behind the RAD diagnoses made in community care, and it is therefore unknown which diagnostic guidelines were used.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, some published papers in academic journals have likewise used a conduct disorder conceptualization of RAD or attachment problems and interpreted results in such a way to suggest that severe behavioral problems are a core feature of RAD (e.g., Hall & Geher, ; Vasquez & Miller, ). Similarly, treatment studies have used this conceptualization, assessed change in severe externalizing problems, and claimed to demonstrate effective treatment for RAD or attachment problems (e.g., Becker‐Weidman, ; Wimmer, Vonk, & Bordnick, ).…”
Section: Introductionmentioning
confidence: 99%